Risk Factors of Injury Severity Level in Foreign Tourists Visiting Bali - Budiapsari, Putu Indah; Widhidewi, Wayan; Muliawan, Ketut Hari; Wirawan, Ady (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2023)
Background: Injuries are the highest cause of death for international tourists, especially injuries caused by traffic accidents. The severity level of injury is the most cause of death. It is necessary to analyze the risk factor of injury severity among international travelers visiting Bali. Purpose: This study aimed to investigate the risk factors for injury severity in foreign tourists visiting Bali. Methods: This cross-sectional analytic study used foreign tourists visiting an international hospital in Bali as the research sample. This research was conducted by analyzing medical records using Injury Severity Score. Data on respondent characteristics, including age, gender, and injury characteristics, including location, type of injury, degree of severity, and injury mechanism, were analyzed using cross-tabulation. Results: The most types of trauma were closed fractures, 49 people (45.4%), and the most common causes were traffic accidents, namely 39 (36.1%) people. Based on the injury region, the lower Extremity is 36 (33.3%) mostly. Conclusion: Age, gender, type of injury, and mechanism of the accident was significant factor influencing the severity of injury among travelers visiting Bali (p0.05).